Hyperbaric Oxygen Exposure Reduces ICAM-1 And HIF1? Expression in Brain Endothelial Cells from Experimental Cerebral Malaria Mice - Prawesty Diah Utami1 , Usman Hadi2 , Yoes Prijatna Dachlan3 , Guritno Suryokusumo4 , Loeki Enggar Fi (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aimed to reveal the role of ICAM-1 and HIF-1? in brain endothelial cell of cerebral malariamice model after exposure to 2.4 absolute atmospheres (ATA) hyperbaric oxygen (HBO). Thirty-nineC57BL/6 mice were divided into three groups: control negative (normal mice without any exposure),control positive (Plasmodium berghei ANKA [PbA] infection without HBO exposure), and treatment (PbAinfection and exposed to HBO for 10 sessions after the parasite grew). Parasitemia and clinical symptomswere observed every day. Brain tissues were isolated on day 13 post-infection for histopathological andimmunohistochemical examination (observed at 400x magnification in 10 visual fields). HBO decreasedHIF-1? and ICAM-1 expression in endothelial cells. There was a moderate correlation between HIF-1? andICAM-1 expression. Ten HBO sessions prevented cerebral malaria, as denoted by the decreased expressionof ICAM-1 and HIF-1? in brain vascular endothelial cells from the experimental mice.